Universal features underlying the magnetism in diluted magnetic semiconductors. (5th March 2018) - Andriotis, Antonis N; Menon, Madhu
Abstract: Investigation of a diverse variety of wide band gap semiconductors and metal oxides that exhibit magnetism on substitutional doping has revealed the existence of universal features that relate the magnetic moment of the dopant to a number of physical properties inherent to the dopants and the hosts. The investigated materials consist of ZnO, GaN, GaP, TiO2, SnO2, Sn3 N4, MoS2, ZnS and CdS doped with 3d-transition metal atoms. The primary physical properties contributing to magnetism include the orbital hybridization and charge distribution, the d-band filling, d-band center, crystal field splitting, electron pairing energy and electronegativity. These features specify the strength of the spin-polarization induced by the dopants on their first nearest neighboring anions which in turn specify the long range magnetic coupling among the dopants through successively induced spin polarizations (SSP) on neighboring dopants. The proposed local SSP process for the establishment of the magnetic coupling among the TM-dopants appears as a competitor to other classical processes (superexchange, double exchange, etc). Furthermore, these properties can be used as a set of descriptors suitable for developing statistical predictive theories for a much larger class of magnetic materials.